The psychological aspect of pain and symptom management in clinical practices: Scoping review - Suantak Demkhosei Vaiphei (National Scientific Medical Center, 2021)
The concept of pain differs as per the individual personal physical, emotional, social, and cognitive-behavior conditions. Pain in its nature of existence is a complex psychoneurotic syndrome that requires a multi-disciplinary inclusive approach to deal with complicated disorders. The psychological issues are a central concern in dealing with pain syndrome, as it resulted in maximizing emotional outbursts and disabilities. The perception of intensity over acute pain syndrome is hugely influenced by the individual immediate context of occurrences. The cognitive-behavioral psychotherapeutic is the one approach that effectively addresses the nature of total pain in the context where it occurs and with the factors that are associated with it. The pain syndrome must be assessed by understanding certain components associated with pain and through the optimal interventions of comprehensive assessment at a multidisciplinary level. The psychopharmacology aspect of pain management in conjunction with the patient's primary needs and comorbidities is a productive assessment method with several positive outcomes